Estimating the Coronal Supra-Arcade Downflow Radio Emission: From Centimeter Through Submillimeter Wavelengths - Zurbriggen, Ernesto; Giménez De Castro, C. Guillermo; Costa, Andrea; Cécere, Mariana; Selhorst, Caius L. (Frontiers in Astronomy and Space Sciences, 2022)
Supra-arcade downflows (SADs) are infrequent, wiggly opaque structures observed to descend through the solar corona, mostly in EUV and soft X-ray frequencies. From their physical characteristics, SADs have been interpreted as voided (subdense) bubbles and are related to magnetic reconnection processes during long-term erupting flares. In this work we use numerical MHD simulations to compute flux density maps, which are convolved with telescope beams to synthesise images with the aim to assess the expected SADs emission at radio wavelengths and propose observing strategies, including the instruments that can be used. We assume that the emission is thermal bremsstrahlung from a fully ionised plasma without any appreciable gyroresonance contribution since magnetic fields are of the order of ∼10 G. We find that SADs emission should be optically thin in the frequency [10 – 1000] GHz range, and the spatially integrated flux should be larger than 1 Jy. We conclude, therefore, that observing SADs in radio frequencies between [0.5 – 1000] GHz is feasible with present instrumentation. Moreover, since the emission is for the most part optically thin, the flux density is proportional to temperature, density and line-of-sight depth, and when combined with EUV and soft X-ray images, may allow a better density and temperature determination of SADs.